2002
DOI: 10.1177/0091270002042009004
|View full text |Cite
|
Sign up to set email alerts
|

Coriolus versicolor: A Medicinal Mushroom with Promising Immunotherapeutic Values

Abstract: Coriolus versicolor (CV) is a medicinal mushroom widely prescribed for the prophylaxis and treatment of cancer and infection in China. In recent years, it has been extensively demonstrated both preclinically and clinically that aqueous extracts obtained from CV display a wide array of biological activities, including stimulatory effects on different immune cells and inhibition of cancer growth. The growing popularity of aqueous CV extracts as an adjunct medical modality to conventional cancer therapies has gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(91 citation statements)
references
References 2 publications
1
88
0
2
Order By: Relevance
“…In fact, although we do not know the chemical composition of L. edodes aqueous extract, it had been demonstrated that aqueous extracts of several mushrooms contain a high concentration of polysaccharides, which could be responsible for the bioactive effects. [17][18][19] Monocytes have an intravascular life span of 1-3 days, leaving the blood stream at random and transforming into macrophages. Macrophages are phagocytes and function to remove foreign bodies, parasites, and bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, although we do not know the chemical composition of L. edodes aqueous extract, it had been demonstrated that aqueous extracts of several mushrooms contain a high concentration of polysaccharides, which could be responsible for the bioactive effects. [17][18][19] Monocytes have an intravascular life span of 1-3 days, leaving the blood stream at random and transforming into macrophages. Macrophages are phagocytes and function to remove foreign bodies, parasites, and bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Genetics are considered to play a relatively minor role, while environment and lifestyle factors contribute to a greater extent to ovarian carcinogenesis suggesting that a window of opportunity exists for chemoprevention of OvCa. Among approaches for chemoprevention, the use of herbal products has gained popularity, particularly those prepared from medicinal mushrooms in light of the traditional high esteem they have held in Asian cultures (4)(5)(6)(7)(8) for promoting and maintaining overall health and wellness, notably through potentiation of immune functions and regulation of biological responses (6)(7)(8)(9)(10)(11). Data have also shown that chemoprevention activities of medicinal mushroom extracts extend beyond the immune system; for instance, evidence abounds that they suppress tumorigenesis further supporting their diverse effects in treating diseases in humans (10,(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…The best known commercial polysaccharopeptide preparations of Coriolus versicolor are Polysaccharide K or Krestin (PSK) and polysaccharopeptide (PSP). Both products are obtained from the extraction of Coriolus versicolor mycelia, PSK is obtained from the extraction of Coriolus versicolor (CM-101) strains, while PSP obtained from the extraction of Coriolus versicolor (Cov-1) strains 88,89 ; PSP and PSK are chemically similar: (1,3) β-glucan branched at 4' and 6' positions and they differ mainly in the presence of fucose in PSK and rhamnose and arabinose in PSP (Figure 3). PSP and PSK are powders that are soluble and stable in hot water.…”
Section: Extracts and Bioactive Compounds Isolated From Coriolus Versmentioning
confidence: 99%